2003
DOI: 10.2508/chikusan.74.355
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Nutritive Value of Tea Grounds Silage Treated with Lactic Acid Bacteria and Acremonium Cellulase

Abstract: The fermentation quality of tea grounds silage added with a selected strain of lactic acid bacteria, Lactobacillus plantarum FG+ and acremonium cellulase (AUS) as additives with a drum silo was studied. Four Su#olk sheep were fed the basal diet with timothy hay and commercial concentration at. : + ratio in dry matter basis. The nutritive value of the tea grounds silage was estimated. After ,1* days of fermentation, tea grounds silages treated with both strain FG+ and AUS were well preserved and exhibited signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 2 publications
0
21
2
Order By: Relevance
“…Addition of dried beet pulp suppressed the disappearance of ECG and EGCG, with changes being almost negligible in EGC and caffeine. Xu et al 15 also reported an inhibited degradation of tea catechins in wet GTW silage when treated with LAB and cell wall degrading enzymes, although their initial contents were substantially lower compared with the residual contents in this study. Bravo et al 16 noted that tea catechins disappeared in large intestine, suggesting that certain microorganisms can degrade tea catechins under anaerobic condition.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Addition of dried beet pulp suppressed the disappearance of ECG and EGCG, with changes being almost negligible in EGC and caffeine. Xu et al 15 also reported an inhibited degradation of tea catechins in wet GTW silage when treated with LAB and cell wall degrading enzymes, although their initial contents were substantially lower compared with the residual contents in this study. Bravo et al 16 noted that tea catechins disappeared in large intestine, suggesting that certain microorganisms can degrade tea catechins under anaerobic condition.…”
Section: Discussioncontrasting
confidence: 41%
“…There is also a variation in the counts of microorganisms in wet GTW, although the reason has not well been studied. Cai et al 3 and Xu et al 15 determined a high number of yeasts with no detectable LAB in the ensiling material, while Kondo et al 2 found a high LAB count. The present study indicated that both LAB and yeasts could be high in wet GTW prior to ensiling.…”
Section: Discussionmentioning
confidence: 99%
“…The organic acid contents were determined by HPLC (Xu et al, 2007). Ammonia-N (NH 3 -N) was determined by steam distillation of the filtrates (Xu et al, 2003) and non-protein nitrogen (NPN) by the Kjeldahl method.…”
Section: Chemical Analysismentioning
confidence: 99%
“…There is increasing demand for efficient use of food by‐products due to economic and environmental concerns. These grounds are usually high in crude protein (CP), amino acids, catechins such as epigallocatechin‐3‐gallate, epicatechin, epigallocatechin and epicatechin gallate, and vitamins (Xu et al . 2003, 2004a; Kondo et al .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there are some problems with using wet green tea grounds (WGTG) as feed, such as a high moisture content, nutritional imbalance, poor preservation and poor intake (Xu et al . 2003; Eruden et al .…”
Section: Introductionmentioning
confidence: 99%